The Impact Of Human Resource Information Systems And Artificial Intelligence On Defense Industry Performance - Riatmaja, Dodi Setiawan; Sukmaningrum, Dinda; Nurcahyo, Narwanto; Saptyawati, Laksmindra (PT. Anagata Sembagi Education, 2024)
The purpose of this research is to investigate how HRIS and AI have influenced the productivity of the military sector in this era of disruption. This inquiry will use a quantitative approach to its methods. The sample pool consisted of one hundred fifty persons who were employed in the military industry. As the main form of data collecting, we will be sending out questionnaires to all of the participants. A Likert scale is provided in the questionnaire, and it is used to assign ratings to the various pieces of information. In order to do an analysis on the data, structured equation modeling in SmartPLS 3.0 was used. In this research, the variable known as